Student perceptions towards the use of the mobile flipped classroom approach - Halili, Siti Hajar (IGI Global, 2021)
This study aimed at identifying students' perceptions in terms of motivation, learning, and engagement in using a mobile flipped classroom approach based on Kolb's learning cycle. This quantitative study was conducted using a questionnaire to collect the data. The collected data were analyzed using descriptive analysis (percentage, means, and standard deviations) utilizing the SPSS 20. The research took place in one of the top private universities in Malaysia and equipped with adequate free internet access. The researcher applied homogenous purposive sampling by selecting 40 undergraduate students registered in the multimedia and computer animation course. The result showed that students had positive perceptions in terms of students' motivation, learning, and engagement in multimedia and animation course using a mobile flipped classroom approach. Future research is recommended to focus on different age and a group of participants to obtain in-depth information on the implementation of mobile flipped classroom approach in a different context. © 2022 American Society of Civil Engineers (ASCE). All rights reserved.